2014
DOI: 10.1007/s12665-014-3264-z
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and chemical variations of ochreous precipitates from acid sulphate waters (asw) at the Roşia Montană gold mine (Romania)

Abstract: The mineralogical and chemical variations of ochreous precipitates forming from acid sulphate waters discharged from the lowest mine adit (“Sf. Cruci din Orlea”) of the Roşia Montană Gold Mine (Romania) were investigated by a multianalytical approach (XRPD, IR, TEM, ICP) applied to surface precipitates and associated waters. The mineralogy of the precipitates changed significantly as a consequence of the variations in the chemical parameters of the circulating solutions (mainly pH, Eh, and sulphate concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…However, stoichiometric Cu to Fe dissolution of chalcopyrite at 650 mV is expected (Figure 1b), regardless of the presence of pyrite, as this Eh is less than the rest potential of pyrite but greater than that of chalcopyrite [38] and little dissolution of pyrite occurs. These findings are of significance in providing better understanding of the factors affecting dissolution rate of mixed chalcopyrite and pyrite systems in AMD systems within the most often observed Eh range of 500-800 mV (SHE) [39][40][41]. In particular the findings suggest that metalliferous Cu-containing drainage may be of importance in this Eh range and that acidic drainage from pyrite dissolution may be partially inhibited if the Eh remains below pyrite's rest potential.…”
Section: Discussionmentioning
confidence: 77%
“…However, stoichiometric Cu to Fe dissolution of chalcopyrite at 650 mV is expected (Figure 1b), regardless of the presence of pyrite, as this Eh is less than the rest potential of pyrite but greater than that of chalcopyrite [38] and little dissolution of pyrite occurs. These findings are of significance in providing better understanding of the factors affecting dissolution rate of mixed chalcopyrite and pyrite systems in AMD systems within the most often observed Eh range of 500-800 mV (SHE) [39][40][41]. In particular the findings suggest that metalliferous Cu-containing drainage may be of importance in this Eh range and that acidic drainage from pyrite dissolution may be partially inhibited if the Eh remains below pyrite's rest potential.…”
Section: Discussionmentioning
confidence: 77%
“…Although a wide range of solution http://dx.doi.org/10.1016/j.gca.2015.04.012 0016-7037/Crown copyright Ó 2015 Published by Elsevier Ltd. All rights reserved. redox potentials (E h ), from negative values to more than 1000 mV (SHE), have been reported for AMD from differing sites (Nordstrom, 2000;Bednar et al, 2005;García et al, 2005;Cheng et al, 2009;Favas, 2013;Hatar et al, 2013), E h in the range of 600-700 mV are most often observed (Costa et al, 2008;Borkowski et al, 2013;Azzali et al, 2014). AMD with pH below 2.0 has also been frequently observed (Dubrovsky et al, 1985;Morin et al, 1988;Alpers et al, 1992;Druschel et al, 2004;Bednar et al, 2005;Costa and Duarte, 2005;Costa et al, 2008;Lu et al, 2011) with, in one extreme case, AMD with negative pH being recorded at Iron Mountain, California (Nordstrom et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Acidic drainage with pH less than 3 and high sulfate concentrations can dissolve and transport environmentally toxic elements such as Zn, Cr, Cu, Ni, Co, Cd, Pb and As, derived from both sulfide and gangue minerals (Azzali et al, 2014), causing serious downstream environmental degradation. Although a wide range of solution http://dx.doi.org/10.1016/j.gca.2015.04.012 0016-7037/Crown copyright Ó 2015 Published by Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on the ochreous precipitates from AMD have shown that the deposits contain a diverse group of iron oxy-hydroxide minerals, in particular, the poorly ordered hydroxysulfates (e.g., jarosite and schwertmannite) that are powerful sorbents for trace metals and oxyanions [ 2 ]. Additionally, the release of heavy metals into the groundwater is associated with Fe(III) oxyhydroxide minerals by dissolution or transformation [ 3 7 ]. Due to the potential ecological and human health risks [ 8 9 ] associated with such a release, the growing awareness of the environmental protection calls for a better understanding of the mineralogical characteristics and transport of metals under extremely acidic conditions of AMD.…”
Section: Introductionmentioning
confidence: 99%